NEW INSIGHTS INTO THE PROTEASOME FUNCTION AND DEGRADATION OF MISFOLDED PROTEINS. (11th November 2018) - Goldberg, A; Lokireddy, S; Kim, H; Kuo, C; VerPlank, J
Abstract: Protein degradation by the UPS is controlled through ubiquitin conjugation and control of proteasome activity. Most 26S proteasomes are in a latent state, but bindings of ubiquitinated proteins enhance its capacity to hydrolyze substrates and stimulates binding of key cofactors. Proteasome function is impaired in major age-related neurodegenerative diseases caused by aggregation-prone proteins. The mammalian proteasome activity can be modulated by agents that raise cAMP and activate Protein Kinase A. PKA stimulates the proteasome's capacity to degrade misfolded and regulatory proteins, by phosphorylation of the 19S subunit Rpn6. Pharmacological agents that raise cAMP stimulate clearance of aggregation-prone mutant proteins that cause tauopathies and ALS, highlighting their potential in treating proteotoxic diseases. Proteasome phosphorylation and activation occur in physiological conditions where cAMP levels rise (i.e. epinephrine-treated hepatocytes or hearts, muscles after exercise, food deprivation). Thus, PKA-mediated proteasome activation is a common physiological response that enhances misfolded proteins degradation.